Correlation between asymptomatic gastroesophageal excessive transmural injury after pulmonary vein isolation and a bonus freeze protocol using the second-generation 28-mm cryoballoon for paroxysmal atrial fibrillation. Issue 6 (December 2019) - Yoshiga, Yasuhiro; Okamoto, Takeshi; Shimizu, Akihiko; Ueyama, Takeshi; Ono, Makoto; Mito, Takahiro; Fukuda, Masakazu; Ishiguchi, Hironori; Omuro, Takuya; Kobayashi, Shigeki; Goto, Atsushi; Nishikawa, Jun; et al.
Highlights: An LET guided cryoballoon ablation carries the risk of a gastroparesis. Gastroesophageal ETI after a cryoballoon PVI was more frequent in bonus freeze group. Strict early interruption due to LET without bonus freeze prevented the ETLs. An additional bonus freeze didn't improve the freedom from AF in the cryoballoon PVI. Abstract: Background: Second-generation cryoballoon (2G-CB) ablation is highly effective for achieving pulmonary vein isolation (PVI) with a promising clinical outcome. However, the ideal freezing strategy for preventing gastroesophageal excessive transmural injury (ETI) remains under debate. This study aimed to clarify the correlation between gastroesophageal ETI and a bonus-freeze protocol after PVI using 2G-CBs. Method: This study included 100 patients who underwent PVI using 2G-CB followed by an endoscopic examination. The freeze-cycle duration was set at 180 s. In the first 33 patients a 120 s bonus-freeze was applied after successful PVI (bonus group), while in the following 67 the bonus freeze was omitted (non-bonus group). Early freezing interruption was performed when the esophageal temperature reached 25 °C. Gastroesophageal ETI was defined as any injury that resulted from the PVI, including esophageal damage or periesophageal nerve injury. Results: Gastroesophageal ETIs were observed in 9 (27.3%) and 6 (9.0%) patients and were all asymptomatic, esophageal damage in 3 and 0, and periesophageal nerve injury in the remaining 6 and 6 in the bonus group and non-bonus group, respectively ( p  = 0.033). In the multivariate analysis, the bonus freeze protocol (odds ratio 3.527; 95% confidence interval 1.110–11.208; p  = 0.033) was the sole independent predictor of gastroesophageal ETI. During a one-year follow-up 26 of 33 bonus group patients (78.8%) and 52 of 67 (77.6%) non-bonus group patients remained in stable sinus rhythm without any differences between the groups. Conclusions: In the patients with a bonus-freeze protocol using the 2G-CB, gastroesophageal ETIs were detected more often than in those with the non-bonus freeze protocol. In contrast, freedom from atrial fibrillation after the 2G-CB based PVI was comparable when applying either a bonus or non-bonus freeze protocol.